Extending social entrepreneurial behaviour research through the integrated theory of sociopreneurial behaviour: a systematic literature review - Arrasyid, Muhammad Iqbal; Sidek, Shafie; Ismail, Noor Azlin; ., Amaliyah (Creative Publishing House, 2024)
Results from prior meta-analyses and systematic literature reviews (SLR) on the formation of Social entrepreneurial behaviour (SEB) have been focusing on the antecedents of social entrepreneurial intention (SEI). However, the impact of the behaviour on welfare and social improvement is essential to distinguish social entrepreneurs from commercial entrepreneurs. Therefore, this article aims to extend the SLR beyond SEI to include any articles related to the formation and impact of SEB. This SLR is carried out in 4 phases. An extensive search in phase 1 has resulted in 332 articles being collected. Filtration in phase 2 resulted in 50 SEI and five SEB articles left for analysis. Descriptive analysis in phase 3 retrieved pertinent general information, such as SEI and SEB research trends, while thematic analysis revealed five theories, six models, and 50 psychological predictors. In phase 4, a systematic researchable framework is synthesised, which is explainable by a proposed theory called the Integrated Theory of Sociopreneurial Behaviour (ITSB). This framework may encourage researchers to identify and verify various external factors that prospectively reinforce or prevent the process of converting SEI into SEB. Besides, the model may suggest more attempts to validate the impact of SEB on the community and sociopreneurs.